Preconditioning elements of cardiac complications among patients with diabetes and acute myocardial infarction - Rosabal García, Yoandro (2024)
Objective: To identify the risk factors based on clinical, echocardiographic and therapeutic parameters which predict the development of cardiac complications among patients with diabetes and acute myocardial infarction (AMI). Materials and methods: An observational, analytical, case-control study was conducted at Centro de Cardiología y Cirugía Cardiovascular de Santiago de Cuba, attached to Hospital Provincial Saturnino Lora, from 2019 to 2021. The sample consisted of 266 patients, chosen by simple random sampling 1:2. The study included demographic, clinicalechocardiographic and therapeutic variables. A multivariate analysis was performed with all the variables considered as risk factors; one-way analysis of variance and binary logistic regression were used. Results: The most frequent cardiac complications were atrial fibrillation and heart failure (approximately 12 %). A metabolic control analysis on admission yielded altered results (OR = 6.92; LI: 2.61; LS: 18.32; p = 0.001). The univariate analysis showed that ten factors increased the risk of complications, including the diagnosis of diabetes mellitus ≥ 10 years (OR = 2.50; LI: 1.14; LS: 5.45; p = 0.020). On the other hand, the multivariate analysis revealed six factors that predict the development of cardiac complications: age ≥ 60 years (OR = 5.624; CI = 1.607-19.686; p = 0.007), altered metabolic control on admission (OR = 5.245; CI = 1.491–18.447; p = 0.010), lack of use of thrombolytic therapy (OR = 5.74; CI = 1.46–22.586; p = 0.012), left ventricular ejection fraction (LVEF) ≤ 40 % (OR = 5.245; CI = 1.17–23.433; p = 0.030), left atrial pressure ≥ 15 mmHg (OR = 12.335; CI = 3.45–44.08; p = 0.001) and motility ≥ 1.5 points (OR = 4.702; CI = 1.258–17.575; p = 0.021). Conclusions: The study demonstrated the value of six risk factors of cardiac complications among patients with diabetes and AMI, where glycemic control on admission, decreased LVEF, increased left atrial pressure and no reperfusion therapy stand out.